Implementation of a business intelligence tool in a hospital billing sector: Applicability and potents - Lavalhos Linke, Leonardo; Zardin Patias, Tiago; Silveira , Sidnei Renato (Journal of Sustainable Competitive Intelligence, 2025)
Objective: This paper presents the process of implementing a Business Intelligence (BI) tool in a hospital billing department, emphasizing its applicability and potential from the perspective of the institution's managers. The general objective of the study was to implement a BI tool in the billing department of the Hospital de Caridade de Palmeira das Missões (HCPM). Methodology/approach: The method chosen for this study was action research. After implementing the BI tool, a semi-structured interview was conducted with four participants directly involved in the process, in order to identify and analyze the applicability and potential of the tool from the perspective of these managers. The data was analyzed using content analysis. Originality/Relevance: The results of the study were structured to highlight the analysis and comparison of BI tools available on the market, as well as defining which would be the most suitable for implementation in the scenario studied, taking into account the advantages and disadvantages of each one and the process of implementing the tool. Main conclusions: Two categories emerged: 1) the tool as a possibility for improving processes and 2) the tool's potential and weaknesses. Based on the implementation of the tool, its use and evaluation by users, it can be concluded that its use provides support for the decision-making processes of the institution's managers, by providing reliable data and information. Theoretical/methodological contributions: The elements discussed in the text validate the proposal to implement the BI tool by optimizing and qualifying the decision-making process.